An Intercultural Experience in European Art and Decorative Design by Chinese Students in Italy - Ha, Sha; Franzin, Maria Rosa (Advances in Social Sciences Research Journal, 2022)
The paper describes the encounter with Italian fine arts and decorative design by a group of 17 Chinese Junior High School, art loving students, during their 2019 summer vacations. According to a ‘cooperative learning’ strategy, the students had been subdivided into four groups, under the guidance of four Chinese teachers, each one responsible for a single group, and the assistance of an Italian artist and an expert teacher herself. During the period of two weeks the students visited historical buildings and museums in the art cities of Venice, Padua, Florence and Rome. In the evening, in the presence of their teachers, they took part to collective discussions on the meaning and impact on them of the most significant art works they encountered during the day. They also took part, in Padua, in an animated ‘active learning’ session in Jewelry Design. That intercultural experience turned out to be very stimulating for those students: part of them included the study of classical art/decorative design in their high school curricula.